A quantitative research of learning habits of secondary school students: An observational study in Dhaka Division - Bipul Kumar Sarker; Nityananda Gain; Sanjoy Kumar Saha; Nilima Bala Mondal; Iftekhar Ifte (Journal of Social, Humanity, and Education, 2024)
Purpose: This study aimed to identify the significant factors influencing the learning habits of secondary-level students. Research methodology: This study examined the learning habits of 120 students from 12 high schools in three categories throughout three surrounding cities in the Dhaka Division. This study used a descriptive survey research design. A Purposive sampling approach was applied to select three districts from the Dhaka division, and 12 secondary schools were selected from the three districts. These 120 respondents were chosen using a simple random sampling method belonging to classes 6–10 and ages 12–16. Results: The average age was 14.0 2.3 years. The majority of the students (39.2%, n = 47) came from families with limited income, and most of their mothers were not working (77.5%, n = 93). Furthermore, most students (39.2%, n = 47) were from poor-class families. Among the three factors influencing learning habits, two (gender and residence status) were statistically significant, but working mothers were statistically insignificant. Limitations: The results of this study may not accurately reflect the entire situation because data from only 120 students from three districts in the Dhaka division were collected. Contribution: There is no statistical relationship between study habits and students’ mothers’ job status. However, gender and residence had an important influence on students’ learning habits. Novelty: The researcher suggests that educators and school authorities work together to convince students how to build efficient study routines and boost their academic and future achievements.